The Effect of Conventional Fertilisation on the Growth and Yield of Palomino Vines on Fertile Soil - Saayman, D.; Conradie, W. J. (South African Journal of Enology and Viticulture, 2017)
The effect of two levels of conventional fertiliser applications on the performance of Palomino grapes on the fertile soil of the Olifants River region was studied. Soil, leaf and must analyses, and shoot and crop mass were used as indicators offertiliser response. A tendency towards improved shoot mass but no significant effect on crop mass due to fertilisation was found. Leaf and must analyses did not reflect treatments, probably because of a natural luxurious P and K supply in the soil concerned, which was calculated to be sufficient for at least 20 years. However, the soil seemed to be on the borderline in its N supplying capabilities for a production level of 40 t/ha. The importance of phylloxera as a growth and production limiting factor in comparison with fertilisation was demonstrated. No P or K fertilisation is recommended for these soils, and a yearly application of 90 kg N/ha is suggested as a guideline for N fertilisation.